Aversive images advertized on cigarette packages: the meanings that assigned by students of a state university in the health area - Souza, Amanda Sena de; Campos, Claudinei José Gomes (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2011)
This qualitative case study was performed with the purpose to analyze the meanings that smoking university students in the health area assign to advertisement using aversive images stamped on tobacco products and the effects on their smoking behavior. A visual presentation of the images was used along with an interview using semi-structured questions applied to ten students in the health area. The data was submitted to thematic content analysis. In conclusion, cognitive behavior does not guarantee a healthy behavior and there is dissociation between the aversive images advertized on cigarette packages and its contents, thus it does not comply integrally with its purpose.